PENGARUH PEMBERIAN BERBAGAI DOSIS MIKORIZA PADA KOMPOS SAMPAH KOTA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max (L.) Merril) DALAM KEADAAN CEKAMAN AIR (Mycorrhizal Doses Effect of Various Cities Compost Trash on Plant Growth and Yields of S - Rendra Afriyon; Nerty Soverda; Nyimas Myrna (Bioplantae, 2012)
The study was conducted in order to see the effect of mycorrhiza on municipal solid waste compost on the growth and yield of soybean under water stress conditions. The research also aims to obtain doses of mycorrhiza plus municipal waste compost is best for the growth and yield of soybean in the state of water stress. The study was conducted using a completely randomized design (CRD) is a factor, giving Mycorrhizae. Media used in all treatments and so on municipal solid waste compost added 200.0 g tan-1 . ie 0 g tan-1 Mycorrhiza, 5.0 g tan-1 Mycorrhiza, 10.0 g tan-1 Mycorrhiza, 15.0 g of tan-1 Mycorrhiza, 20.0 g tan-1 Mycorrhiza. Each treatment was repeated 4 times, so to get 20 units of the experiment. Observation of the results were analyzed by analysis of variance, followed by the Least Significant Difference Test (BNT) with level α = 5%. Based on the analysis of variance in the observed variables shows that mycorrhizal administration at a dose of 5.0, 10.0, 15.0 and 20.0 g of tan-1 at the city compost in a state of water stress significant effect on the number of leaves and number of primary branches. But did not significantly affect plant height, dry weight , root dry weight, number of pods per plant, number of pods per plant contains, 100 seed weight, and yield per plant.Key words: Soya bean, stress, mycorrhiza